Analysis of Junior High School Student’s Errors in Solving Mathematical Connection Problems on Quadrilateral Topics - Hanne Ayuningtias Elsa; Suhendra Suhendra (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
Mathematical connection is one of the abilities that need to be possessed by students because it can help students in obtaining meaningful knowledge. However, there are still some junior high school students who have difficulty in solving problems related to mathematical connections on quadrilateral topics, thus allowing errors to occur. The purpose of this study was to obtain a description of the errors of junior high school students in solving mathematical connection problems on quadrilateral topics. This type of research is qualitative research with a case study design. This research was conducted by giving mathematical connection test questions to class VIII junior high school students consisting of three essay questions on quadrilateral topics and the topic of broad expansion in science lessons, as well as conducting interviews with nine selected students. The results showed that there were four types of errors made by students based on Newman's Error Analysis, namely eight answers to problem understanding errors, nine answers to transformation errors, 15 answers to process skills errors, and six answers to writing answer errors. Keywords: errors, mathematical connection, Newman’s Error Analysis, quadrilateral